Subwencja ogólna dochodem wyrównawczym dla jednostek samorządu terytorialnego na przykładzie gmin wiejskich województwa dolnośląskiego - Milewska, Anna (General Subvention - Compensation Income of Local Government Units (on Example of Rural Communes of Dolnośląski Voivodship), 2005)
The aim of this article is to show differences of rural budgets. The author analysis functioning of communes in Poland, the importance of general subsidies for their incomes, and for the whole budget of these communes. The author studies how to average the rural communes in province compared to all communes in the province and how to average the rural communes in the whole country compared to all communes in Poland.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 103-107